The Divine Providence - Dole, Charles F. (Harvard theological review, 1908)
The belief in a doctrine of Providence, at least in some sense of the word, is inseparable from theism. Let a man once assume a good God or a righteous universe, and he thereby also assumes that all events must be directed, or at least overruled, for good. Perhaps, however, it is a little easier to declare what one means when he says, “there is a God,” than to explain what one means by “the divine Providence.” Do we believe in a special Providence, that enters into each particular act or moment, so that, for example, it is literally true that not a sparrow “shall fall to the ground without your Father”? Do we think that the infinite Power carries every individual life in its thought, and even plans, and cares what each man does, suffers, or enjoys? Or do we think of Providence as merely a general guiding agency, like the intelligence that steers a ship in safety without any special responsibility for the conduct or the pleasure of the passengers? Do we think that a man can interfere, by the exercise of his little will, with the working of divine Providence? Or does Providence also enter into and direct the motion of every individual will, as it may be conceived to enter into the motion of the sands on the beach?